Diagnostic Evaluation of Pregnancy Detection Methods in Dairy Cattle - Jasrotia, Nancy; Chandra, Pradeep; Athidi, Lokavya; Patra, Manas Kumar; Kumar, Brijesh; Singh , Sanjay Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The objective of the present study was to evaluate the diagnostic potential of pregnancy detection methods at an early stage in cattle  using transrectal ultrasonography, per-rectal palpation and commercially available PAG based ELISA kit. The study was conducted on 116  crossbred cyclic cows, aged 3-8 years. The cows at estrus were artificially inseminated using 2 doses of quality semen at 10-12 h interval.  They were subjected to trans-rectal ultrasonography and PAG test in randomized animals at around 28-35 days’ post-insemination. The  animals were further examined by second trans-rectal ultrasonography and per-rectal palpation on day 45-50 post-AI. Ultrasonography  was found to be more effective in diagnosing early pregnancy followed by PAG test around day 28 and per-rectal examination by day  45-50 post-insemination. However, PAG test was more accurate in diagnosing open cows at the earliest.
Keywords: Cattle; ELISA; PAG; Per-rectal palpation; Pregnancy diagnosis; Ultrasound